2013
DOI: 10.2741/s378
|View full text |Cite
|
Sign up to set email alerts
|

Biomimetic materials for controlling bone cell responses

Abstract: Bone defects that cannot "heal spontaneously during life" will become an ever greater health problem as populations age. Harvesting autografts has several drawbacks, such as pain and morbidity at both donor and acceptor sites, the limited quantity of material available, and frequently its inappropriate shape. Researchers have therefore developed alternative strategies that involve biomaterials to fill bone defects. These biomaterials must be biocompatible and interact with the surrounding bone tissue to allow … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 235 publications
0
12
0
Order By: Relevance
“…Existing literature describing BTE scaffolds bioinspired by bone tissue architecture has shown that their microtopography can control cellular responses through scaffold-cell interactions that activate proliferation and osteogenic differentiation pathways [ 12 ]. The oriented microstructures of scaffolds guide the elongation and growth-orientation of the cells seeded on and into them.…”
Section: Introductionmentioning
confidence: 99%
“…Existing literature describing BTE scaffolds bioinspired by bone tissue architecture has shown that their microtopography can control cellular responses through scaffold-cell interactions that activate proliferation and osteogenic differentiation pathways [ 12 ]. The oriented microstructures of scaffolds guide the elongation and growth-orientation of the cells seeded on and into them.…”
Section: Introductionmentioning
confidence: 99%
“…As seen, biomaterials are key: besides harbouring viable stem cells and bioactive molecules, a biomaterial used in bone tissue engineering, or one used as a bone substitute, needs to be bioabsorbable, possess sufficient mechanical stability, and mimic the complex porous architecture of bone extracellular matrix (ECM). All these requirements have prompted research on materials bio-reactivity and driven the appearance of the fourth generation of biomaterials: the socalled biomimetic or smart materials (2,3).…”
Section: -Introductionmentioning
confidence: 99%
“…There are many other challenges in the use of peptides-functionalized surfaces, such as the way they are immobilized on the surface to retain their bioactivity, their density and conformation (248). Rezania and Healy compared the effect of peptides derived from BSP (CGGNGEPRGDTYRAY) immobilized on a quartz surface at densities from 0.01 to 3.8 pmol/cm² on the osteoblastic differentiation of rat calvaria osteoblast-like cells (249).…”
Section: Gggggggfhrrikamentioning
confidence: 99%